Comparison of Intralesional Kenacort Injection Versus Surgical Intervention for Primary Chalazion - Muhammad Nasir Bhatti, Narain Das, Asma Shams Beenish Khan (Pakistan Journal of Ophthalmology, 2019)
Purpose: To compare the efficacy and safety of intralesional steroid injection versus surgical intervention (Incision and Curettage) in Primary Chalazion. Study Design: Prospective, comparative and interventional hospital based study. Place and Duration of Study: Shaheed Mohtarma Benazir Bhutto Medical College Lyari and Sindh Government Lyari General Hospital, Karachi from 15th October, 2016 to 15th April, 2017. Material and Methods: All patients diagnosed with chalazion on clinical basis from the Outpatient department of Ophthalmology were included in the study. All patients were randomly divided into two groups with 25 patients in each group. Group 1 received intralesional 0.2 ml triamcinolone acetonide while Group 2 received surgical intervention (Incision and Curettage). Results: There were 50 eyes of 50 patients between the age group of 15 to 40 years and of either gender. Mean age was 25 ? 12.2 with male to female ratio of 2:1. There were 19 (76%) patients who achieved complete resolution of chalazion after intra-lesional triamcinolone acetonide in group I and there were 21 (84%) patients out of 25 who achieved complete resolution of chalazion after incision and curettage in group II. No ocular complication such as bleeding, elevation of intra ocular pressure, eye lid de-pigmentation or any loss of vision in either group was observed. Conclusion: Intralesional triamcinolone acetonide injection is nearly as effective as surgical treatment (incision and curettage) in primary chalazion. Keywords: Triamcinolone, Chalazion, Eyelid Diseases.